2002
DOI: 10.1046/j.1360-0443.2002.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

European adolescent substance use: the roles of family structure, function and gender

Abstract: Living with both parents is a less robust barrier to substance use than qualitative aspects of family life, particularly attachment to mothers. The latter is a robust inhibitor of substance use irrespective of regional differences in drug availability, weakening only in the face of more generally problematic behaviour. Perhaps because of their greater tendency to risk-taking or rule breaking, supervision appears more important for male than female drug use. These findings underscore the role of families, but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 33 publications
10
79
1
8
Order By: Relevance
“…Therefore socioeconomic status was unlikely to be a main factor for the paternal-maternal differences observed. Some studies have reported that the effect of family structure on substance use differed significantly by sex [20,46], but this was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore socioeconomic status was unlikely to be a main factor for the paternal-maternal differences observed. Some studies have reported that the effect of family structure on substance use differed significantly by sex [20,46], but this was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 95%
“…However, contradictory findings have also been reported. While there were findings to support the association between non-intact family structure and higher alcohol drinking frequency among adolescents [19], others found no relation between them [20]. Relatively few studies have further classified single-parent families into paternal or maternal families [16,21-23], and none has made statistical comparisons between them in relation to adolescent substance use, and considering the effects of parent-child communication [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Although the definition and structure of a family (e.g., nuclear, extended) varies between countries and across cultures, the power of a family can be harnessed in HIV prevention and control, assuming cultural concerns about privacy of persons and confidentiality of data are addressed appropriately. Several investigators have pointed to the importance of families in substance use addiction or called for interventions that build on the strengths of the families and mobilize them to contribute to the community's long-term health, survival, and security needs (Aronowitz et al, 2005;Fullilove et al, 2000;McArdle et al, 2002;Paruk et al, 2005;Rotheram-Borus et al, 2005).…”
Section: Levels Of Risk Reduction Interventionsmentioning
confidence: 99%
“…Social factors such as lack of parental monitoring (McArdle et al, 2002), certain peer groups and schools, and attachment to substance abusing peers (Dupre et al, 1995) have been shown to be significantly associated with the risk of early initiation. Change in maternal marital status, particularly when the child is 5-14 years old, is also associated with an increased risk of cannabis use (Hayatbakhsh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%